1970
DOI: 10.1136/adc.45.239.80
|View full text |Cite
|
Sign up to set email alerts
|

Transient Neonatal Diabetes Mellitus in Sibs

Abstract: The infant was breast-fed and sucked well. However, he failed to gain weight, and on the 15th day began to vomit occasionally. On the 19th day he was transferred to the Children's Ward for further investigation. He then weighed 2065 g., was marasmic, wide-eyed, and thirsty, with a rectal temperature of 39*4 'C.( Fig.). Blood sugar, 720 mg./100 ml.; CSF sugar, 405 mg./100 ml.; CSF protein, chloride, and cell count normal; blood urea, 77 mg./100 ml.; urine contained 2% sugar but no ketones.A subcutaneous infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…Two explanations have been offered for this condition: insulin deficiency or insulin resistance. The evidence from the present study confirmed the viewpoint expressed previously (Ferguson and Milner, 1970) that transient neonatal diabetes is due to delay in functional maturation of the fetal :-cell.…”
Section: Discussionsupporting
confidence: 92%
“…Two explanations have been offered for this condition: insulin deficiency or insulin resistance. The evidence from the present study confirmed the viewpoint expressed previously (Ferguson and Milner, 1970) that transient neonatal diabetes is due to delay in functional maturation of the fetal :-cell.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the effect of the exogenous insulin in bringing the diabetic state under control was very striking in this infant, suggesting that the tissues themselves were very sensitive to the effect of insulin. This phenomenon has already been well documented in similar cases (Hutchison, 1967;Ferguson and Milner, 1970). At the age of 1 month when the glucose tolerance test repeated, the blood glucose levels showed an entirely normal configuration, but once again, though the fasting insulin level was well within the normal range, there still appeared to be an exaggeration in the insulin response.…”
Section: Discussionsupporting
confidence: 65%
“…The kG value of 1-2 was within the normal range for that age group, and the insulin levels showed the expected changes. Ferguson and Milner (1970) suggested that transient neonatal diabetes might be due to delay in the maturation of the fetal P-cells, and that the delay might be due to a combination of maternal and placental factors. Steiner and his colleagues (1968) have shown that the purified fractions of proinsulin all react with antisera to insulin, but in the purified intact form, proinsulin has very low biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported examples of temporary neonatal hyperglycaemia have invariably been in babies small for their gestational age, and the presenting feature has been jitteriness (Lewis and Mortimer, 1964;Geefhuysen, 1966;Chance and Bower, 1966;Ferguson and Milner, 1970). Furthermore, the plasma insulin level was low at the time of the hyperglycaemia, as has been recorded by Gentz (1969) in 2 affected babies.…”
Section: Discussionmentioning
confidence: 79%